The Evaluation of Horizontal Alignment Design: A Case Study of Jalan Tarikolot Majalengka - Yudi Herdiana; Andri Irfan Rifai; Mohamad Taufik; Joewono Prasetijo (Pelopor Publikasi Akademika, 2024)
Road geometric design is a way of planning a road geometrically or involves calculating angles through the process. Regarding the geometric design of roads, it is important to assess the conformity of the design criteria with the applicable guidelines, namely the Road Geometric Design Guidelines. In this paper, an eval_uation of the geometric design of existing roads, namely Jalan Raya Tarikolot, Majalengka, and adjustments to the Road Geometric Design Guidelines is carried out. The research method used is an eval_uation research method for the research object, namely Jalan Raya Tarikolot, Majalengka. The results obtained show that Jalan Raya Tarikolot, Majalengka is a road with a flat terrain type. Alignment P2 is the FC alignment type, while the other seven alignments are S-C-S alignment types. Through the eval_uation carried out, the results showed that the horizontal adjustment of the Tarikolot Highway, Majalengka met the criteria, so it did not require design improvements.